Ekstradisi Pelaku Tindak Pidana Korupsi yang Melarikan Diri Keluar Negeri Oleh Kepolisian Negara Republik Indonesia Berdasarkan Ketentuan Hukum International Criminal Police Organization (ICPO/Interpol) - Dio Poliando Panggabean (USU LAW JOURNAL, 2019)
Abstract. Interpol is an organization which is formed to coordinate cooperation between police throughout the world. The intensity of crime increasing and very sophisticated technology is used nowadays makes it easier for criminals to flee outside their country's territory. The extradition treaty plays an important role in being able to arrest suspects of criminal acts of corruption who have escaped abroad so that the law enforcement process can be carried out against the suspected perpetrators of corruption in Indonesia. The formulation of the problem in this study is how is the general legal regulation of international criminal police organizations (ICPO/ Interpol) in the field of extradition of perpetrators of corruption crimes who have fled abroad, how the extradition mechanism of perpetrators of corruption in Indonesia has escaped the country carried out by the Indonesian police and how the obstacles faced by the Indonesian national police in carrying out international cooperation. The results of the discussion of the problems that arise in this study are international cooperation agreements that have been ratified by the two countries, where the Indonesian police submitted a request to the state government where the perpetrators of corruption have escaped. The requested state government processes the extradition request by requesting authentic evidence of the perpetrator's complete identity. The process of implementing extradition is hampered because there is no international cooperation agreement in the field of extradition which has been ratified by the Indonesian government with the state government where the perpetrators of corruption have escaped, so that the request for extradition is rejected by the state.   Keywords: corruption; ICPO ;Interpol; fleeing abroad.